Fishing season of large pelagic fish in Idi Rayeuk waters, East Aceh, Indonesia - M.A. Chaliluddin; Rizka Alfita; Thaib Rizwan; Rahmat Rizqi; Rosi Rahayu; Sayyid Afdhal El Rahimi; Ichsan Rusydi (Depik, 2021)
Large pelagic fish live on the water surface in groups. Skipjack tuna (Katsuwonus pelamis), yellowfin tuna (Thunnus albacares), mackerel tuna (Euthynnus affinis), mackerel (Scomberomous guttatus) are species of fishes that mainly catches by fishermen using purse seines. This study aims to determine the length and weight of large pelagic fish in the water of Idi Rayeuk and best the fishing season. This research was conducted in one month. Fish samples were collected from fishermen that used purse seine and landed their catches at the Idi Rayeuk Fishing Port, East Aceh. Additionally, the data was derived from the fishing port time-series during 2015 to 2019. The result showed that the yellowfin tuna (Thunnus albacares) has a length between 37 - 58 cm with a weight of 1.0 - 3.2 kg, skipjack tuna (Katsuwonus pelamis) 32 - 58 cm in length and weight 0.5 - 3.0 kg, mackerel tuna has 33 - 54 cm of length with a weight of 0.6 - 2.5 kg, and mackerel has 44 - 66 cm of length and weighing 0.7 - 1.7 kg. Its also found that the peak season for catching yellowfin tuna (Thunnus albacares) and mackerel tuna is May and June, and the lowest season in December for the yellowfin tuna, and December and January for the mackerel tuna. The peak season for skipjack fishing occurs in May, August, and October, and the low season occurs in November and December. Meanwhile, the peak season for fishing mackerel occurs in May, September, and October, while the low season occurs in January, February, and March.Keywords:Fishing seasonLarge pelagicPurse seineIdi RayeukAceh